Human Development Management as the Basis for the Pre-Adaptation of Complex Systems in Conditions of Uncertainty and Unpredictability - Gubanova, Svetlana (Տիգրան Մեծ)
The article is devoted to the issue of managing the balanced development of human potential in a new socio-economic reality, which is characterized by a high degree of unpredictability, interconnectedness and interdependence, globalization and informatization of the environment and introduction of digital, cognitive and hybrid technologies. There is a need to recognize the dominant role of scientific knowledge and creative implementation, wise management and consumption. For the first time, the term “noo-management” was introduced: it is a method of intelligent management of the fundamentalprocesses of personality development focused on higher-order values and creative implementation.
Keywords: Philosophy